The food retail market and the Common Agricultural Policy in the Nordic countries and the countries applying for EU membership - Ágúst Einarsson 1952- (2012)
Ritrýnd grein This paper describes the food retail market in the Nordic countries and in the countries applying for EU membership and analyses the impact of reforms of the Common Agricultural Policy (CAP) in the EU. Three of the Nordic countries (Denmark, Finland and Sweden) are member states of the EU, while Iceland and Norway are not, although Iceland is applying for EU membership, as are Albania, Croatia, Macedonia, Montenegro, Serbia and Turkey. Profound changes have occurred in the agricultural sector in the past years in all these countries. The reforms of the CAP approved in 2003 represent the most radical CAP reforms in the history of the EU. In the paper the resulting changes are discussed, as are the planned world trade reforms currently being negotiated within the World Trade Organization (WTO). Among the issues decided within the WTO are tariff regulations, where there is a wide divergence between the views of developed countries and developing countries. The paper proposes an assessment of the impact of the CAP reform and the WTO negotiations on the Nordic countries and the applicants. Í greininni er lýst markaði fyrir matvæli á Norðurlöndunum og í þeim löndum sem hafa sótt um aðild að Evrópusambandinu og greind eru áhrif umbóta á almennu landbúnaðarstefnu Evrópusambandsins. Þrjú Norðurlandanna, Danmörk, Finnland og Svíþjóð eru aðildarríki Evrópusambandsins en Ísland og Noregur eru það ekki. Ísland hefur sótt um aðild eins og Albanía, Króatía, Makedónía, Serbía, Svartfjallaland og Tyrkland. Miklar breytingar hafa orðið á undanförnum árum í landbúnaði innan allra þessara landa. Umbætur á almennu landbúnaðarstefnu Evrópusambandsins voru samþykktar árið 2003 og það eru umfangsmestu breytingar sem hafa verið gerðar á stefnunni í sögu Evrópusambandsins. Í greininni eru þessar breytingar ræddar svo og hinar ráðgerðu umbætur á heimsverslun með matvæli sem eru til umræðu á vettvangi Alþjóða viðskiptastofnunarinnar. Meðal þeirra atriða sem er rætt um innan Alþjóða viðskiptastofnunarinnar eru tollamál og ...